Hubungan Kompetensi Perekam Medis dan Informasi Kesehatan dengan Kinerja dalam Melaksanakan Praktik Rekam Medis dan Informasi Kesehatan di Fasilitas Layanan Tingkat Pertama - Karmanto, Bambang; Natalia, Eri; Elfi, Elfi (Poltekkes Kemenkes Kendari, 2023)
The goal of competency is getting a result from encouragement or motive. Meanwhile, performance is a function that describes the indicator of competency which are knowledge, skills, behavior, and experience to carry out a job or role effectively. Medical recorders and health information technicians in public health centers must comply with the competencies contained in KMK No. 312 of 2020. The study's purpose is to determine the relation of Medical recorders and health information technicians with performance in implementing medical record practices and health information in first-level health services facilities. The research uses observational and cross-sectional approach methods. The sample is all Medical recorders in the public health center in Cirebon City that 32 medical recorders and health informations technicians. The univariate test shows that medical record and health informations technician competency in 50% for the capable category. Meanwhile, the performance in 59,4% for the good category. The output of the chi-square test process shows a p-value of 1,000> 0,05. It means that there's no relationship between medical recorders and health informations technician competency with performance in implementing medical record practices and health information in first-level health services facilities. To improve medical recorder competency and performance, should have been held such as training, socialization, dissemination, and case discussion.